Outcome analysis of vacuum assisted closure therapy in patients with open wounds - Jain, Ravi Kant; Mohammad, Danish; Mahajan, Pranav; Sheikh, Tanveer; Rege, Awyay (International Journal of Research in Orthopaedics, 2017)
Background: Vacuum assisted Closure (VAC) of wound is a recent trend and proven method of fast and better healing of wounds. The basic concept is the removal of blood and serous collection from the wound site with negative pressure and promoting the healing process rapidly by altering the local microcellular environment.The objective of the study was to show the efficacy of healing process in open wounds treated by VAC method of dressing. Methods: In this prospective study, total of 50 patients with upper and lower limbs non-healing open wounds were recruited. Before the application of VAC, surgical debridement was performed to remove all the devitalized necrotic tissues and the wound was packed with povodine iodine. Prior to and at the end of VAC dressing, wound dimensions were noted. Results: Patients mean age was 46.72±7.63 years and out of which 42 patients (84%) were males and 8 patients (16%) were females. All patients had suffered an acute trauma. VAC therapy was applied through continuous or intermittent suction on wounds and dressing were changed every second or third day. After application of VAC therapy all wounds showed improvement, which were indicated by presence of healthy granulation tissue, absence of necrotic tissue and subsequent wound closure. Conclusions: VAC dressing in an open wound is an efficient and safe adjunct to treat severe infections and may be a good alternative to treat the open wounds in selected patients. Short time intervals between VAC changes and short course of therapy result in good patient acceptance. This method is recommended for all the types of non-healing wounds management.